Environmental constraint of intraguild predation: Inorganic turbidity modulates omnivory in fairy shrimps. (20th October 2019) - Lukić, Dunja; Ptacnik, Robert; Vad, Csaba F.; Pόda, Csenge; Horváth, Zsόfia
Abstract: Omnivory is widespread in food webs, with an important stabilising effect. The strength of omnivorous trophic interactions may change considerably with changes in the local environment. Shallow temporary waters are often characterised by high levels of inorganic turbidity that may directly limit the food uptake of filter‐feeding organisms, but there is little evidence on how it might affect omnivorous species. Anostracans are key species of temporary waters and recent evidence suggests that these organisms are omnivorous consumers of both phyto‐ and zooplankton. Using Branchinecta orientalis as a model species, our aim was to test how turbidity affects the feeding of an omnivorous anostracan. To do this, we used short‐term feeding experiments and stable isotope analyses, with animals collected from soda pans in eastern Austria. In the feeding experiments, algae and zooplankton were offered as food either separately or in combination. The prey type treatments were crossed with turbidity levels in a factorial design. There was a pronounced decrease in the ingested algal biomass with increasing turbidity. Conversely, ingestion rates on zooplankton were less affected by turbidity. Stable isotope analyses from field material supported our experimental results by showing a positive relationship of the trophic position of anostracans and the trophic niche of the communities with turbidity. Our results show that turbidity modulates the intraguild trophic relationship between anostracans and their prey by shifting the diet of anostracans from more herbivorous in transparent to more carnivorous in turbid waters. Thus, inorganic turbidity might also have a community‐shaping role in plankton communities of temporary waters through altering trophic relationships.